Program Kaligrafi dalam Membangun Jiwa Gotong Royong Sebagai Penerapan P5 Kurikulum Merdeka di SD Negeri 79 Kota Bengkulu - Adel Febrianti; Meisi Dwi Wulandari; Niken Aprilia Azhari; Ola Anjani (UIN Fatmawati Sukarno Bengkulu, 2025)
The purpose of this study is to describe the implementation of P5 Gotong Royong activities in learning Islamic Religious Education. The method used is descriptive qualitative. Based on the findings at SDN 79 Bengkulu City, the researcher concluded that Calligraphy activities are considered appropriate to improve students' mutual cooperation spirit in accordance with Islamic teachings and foster love for the Qur'an. This is because planting activities will increase students' awareness of the importance of loving Allah's Verses. The P5 project on the mutual cooperation dimension through the Calligraphy making project that has been implemented at SDN 79 Bengkulu City is relevant to the objectives of the P5 content in the achievements of the P5 project activities. It can be seen from the observation that students are happy because they can work together, help each other, share opinions in carrying out this P5 Calligraphy learning activity. From the documentation obtained, it shows that the implementation of P5 learning on the mutual cooperation dimension in the Calligraphy project is in accordance with the objectives of P5 learning itself. The achievement of P5 learning on the mutual cooperation dimension is very good as seen from the results of the reflection carried out by the teacher at the end of learning. Most students are happy with this P5 learning because they can work together, share, and help each other. So the dimension of mutual cooperation has been considered successful.